On a Paraguayan sample of a long time confused species: Physalaemus fuscomaculatus (Steindachner, 1864) (Anura, Leptodactylidae) - Cei, José Miguel Alfredo María (1990)
The poorly known taxon Physalaemus fuscomaculatus (Steindachner, 1864) is now defined and illustrated on the basis of a still unidentified sample of Paraguayan specimens from the Zoological Museum of Turin, Italy, collected in 1893 by A. Borelli close to Rio Apa, atributary of the Paraguay River. The comparison of such a sample with Steindachner’s/holotype was earned out and a suitable iconographie documentation is presented. The identity of Steindachner’s holotype and Borelli’s sample was unquestionably supported, and a new suitable description of the species, on the basis of the original description, is now available. This paper contributes to clarify more than a century of taxonomic confusion, having been long time neglected Physalaemus biligonigerus (Cope, 1860) owing to a misled diagnosis of Physalaemus fuscomaculatus (=Paludicola fuscomaculata) since Boulenger’s time.